Future in sight 100 trends, implications & predictions that will most impact businesses and the world economy into the 21st century - Minkin, Barry Howard (Macmillan, 1995)
This guide describes the 100 most likely trends of the coming decade. Using business insight and the professional counsel of 200 business people, it provides advice for future business, investment and personal living.